ANALISIS PENGEMBANGAN OBYEK WISATA UMBUL PONGGOK DALAM USAHA PENINGKATAN PEREKONOMIAN MASYARAKAT DI DESA WISATA PONGGOK KECAMATAN POLANHARJO KABUPATEN KLATEN - Kusumastutik, Anjelia; Sugiyarti, Sri Riris; Winduro, Wirid (Solidaritas, 2024)
Tourism object development is a process that emphasizes how to develop or advance a tourist village, this has an impact on improving the economy of the community in Ponggok Tourism Village. The purpose of this research is to describe the development of Umbul Ponggok Tourism Object in an effort to improve the economy of the Ponggok Village community. This research uses qualitative research methods with a descriptive approach. The theory used is Cooper's theory with the dimensions of Attraction, Accecibility, amenity, and anciliary. Data collection was carried out using interview techniques and documentation. The data analysis technique used is an interactive analysis technique. The technique of determining this informant uses Purposive Sampling technique. The informants of this research consisted of BUMDes Marketing Manager, MSME players, and visitors to Umbul Ponggok Tourism.The results of this study indicate that the development of Umbul Ponggok with an attraction to Walker Ponggok is successful, road accessibility is actually good, but if it intersects with large trucks it is a little difficult to pass, supporting facilities are actually complete but need to be improved again, and supporting institutions that are given good training on services, have had a positive impact on improving the community's economy.Keyword : Tourism development, tourism village, economic improvement